Pengaruh Senam Tera Terhadap Penurunan Nyeri Sendi Pada Lansia di PSTW Sabai Nan Aluih Sicincin - Adep Junika; eliwarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
Joint pain is a very common health problem among the elderly in Indonesia. To treat joint pain various treatment approaches are available, which are usually divided into two main categories, namely pharmacological and non-pharmacological. One way to treat joint pain by providing non-pharmacological therapy is by doing tera exercises for elderly people who suffer from joint pain. Tera gymnastics is an effective non-pharmacological approach in managing joint pain in the elderly with various exercise components designed to increase flexibility, strength, balance and coordination. The aim of this study was to determine the effect of tera exercise on reducing joint pain in the elderly at the Tresna Nursing Home Sabai Nan Aluih Sicincin. This type of research is quantitative experimental. Using a one group pre-test and post-test design. The number of samples taken was 10 elderly people at PSTW Sabai Nan Aluih Sicincin using the random sampling technique. The instrument used in data collection was a questionnaire, data was analyzed via SPSS using the paired sample t-test. The results of the study showed that there was a significant effect before and after giving tera exercises to elderly people with joint pain with a p-value of 0.000. The results of this research can be used as an alternative to increase the knowledge of elderly people in reducing joint pain, especially by using tera exercises